Earth treasures : rocks and minerals - Comfort, Iris Tracy (Englewood Cliffs, N.J. : Prentice-Hall, 1964)
Discusses the formation, properties, and uses of different kinds of rocks and minerals
Keywords: Rocks -- Juvenile literature; Mineralogy -- Juvenile literature